EFFECT OF SUBLETHAL CONCENTRATIONS OF CYPERMETHRIN ON SOME HAEMATOLOGICAL PARAMETERS OF THE FRESHWATER FISH Oreochromis niloticus IN STATIC BIOASSAY - YAJI, A. J.; AUTA, J.; ONIYE, S. J.; ADAKOLE, J. A.; SOLOMON, V. (Nigerian Journal of Fisheries, 2012)
Study was carried out to determine the haematological responses of Oreochromis niloticus exposed to cypermethrin. Juveniles were exposed in aquaria of 20 l capacity containing 0.0005, 0.001, and 0.002 mg/l sublethal concentrations of cypermethrin. Haematological analysis of the blood of fish examined showed that Red blood cell counts (RBCC), and haemoglobin (Hb), and packed cells volume (PCV) decreased significantly (P < 0.05) as the concentration of the toxicant increase. The mean corpuscular volume (MCV) significantly (P < 0.05) increased with fish exposed to 0.001 mg/l concentration of the toxicant when compared with control value, but were lower significantly (P < 0.05) with those fish in the highest concentration (0.002 mg/l) concentration. Mean corpuscular haemoglobin (MCH) and Mean corpuscular haemoglobin concentration (MCHC) between the control and the exposed groups did not vary significantly. White blood cell counts (WBCC) increased significantly (P < 0.05) as the concentration of the toxicant increased. Similar trends were observed during week 6 exposure periods, RBCC, Hb, and PCV values of fish reduced significantly (P < 0.05) with fish exposed to ≥ 0.001 mg/l concentrations. MCV of fish recorded significant higher (P < 0.05) values in exposed groups at concentrations ≥ 0.001 mg/l. Values were highest with fish exposed to 0.001 mg/l and lowest in the highest concentration (0.002 mg/l, while MCHC values were not significant with exposed fish compared to the exposed groups. Percentage neutrophils of the control fish were significantly lower (P < 0.05) than those exposed to ≥ 0.001 mg/l sublethal concentrations of cypermethrin, but significantly higher (P < 0.05) than fish exposed to 0.0005 mg/l. Percentage lymphocytes of the control group were significantly lower (P < 0.05) compared to fish exposed to 0.000 and 0.001 mg/l concentrations of the toxicant. No traces of basophils, eosinophils, and monocytes found.